Frequency of Vernal Kerato-conjunctivitis (VKC) and its Complications in Patients Presenting at District Headquarter Hospital, Sheikhupura - Muhammad Awais Asghar; Amina Muqaddas; Kiran Iftikhar; Shehrish Kamran; Mishel Zainab; Musa Ali Irfani; Usman Ayub Awan (BioScientific Review, 2022)
Vernal Kerato-conjunctivitis (VKC) is an allergic illness that affects the eyes and causes the inflammation of conjunctiva, which is commonly bilateral. If left untreated, it may lead to serious consequences such as redness, stinging, and watering of the eyes, resulting from papillae, Horner-Trantas spots, and punctate epithelial lesions. The current study aimed to determine the prevalence of VKC in the Out-Patient Department (OPD) of Ophthalmology at the District Headquarter Hospital, Sheikhupura. VKC was diagnosed in 40 individuals between May and June of 2021. The majority of them were young men who were less than 20 years old. Indeed, it was found that VKC is more prevalent in children and men. Around 57.5% of children in our study were boys, whereas 42.5% were girls. Almost every single one of them was less than twenty years of age. Among the various age groups, it was found that the age group (6-10 years, n=18) had the highest prevalence of VKC cases, followed by the age group (n=11) (1-5 years). To prevent patients from developing illness consequences that negatively impact their quality of life, VKC must be handled promptly and with diligent follow-up. To conclude, the current study found that VKC in Pakistan follows a pattern similar to other tropical nations, with male predominance and higher prevalence during infancy and puberty.